Some Reasons for the Lack of Success When Learning Mathematics in Technical Universities and Recommendations for Their Overcoming [In Bulgarian] - K. Dishlieva (University of Sofia, 2014)
A brief overview of the objective criteria and unified standards in tertiary technical education, developed and controlled by European professional associations is done. The reasons are given for which engineering mathematics is a serious barrier for the students in technical universities - lack of the constructive relationships between: universities and secondary schools; teachers and students in the learning process; discrepancies in the curricula of different university departments. The interdisciplinary approach is not used as a factor of motivation at different levels, and the contemporary teaching tools and methods are missing as well. The knowledge and skills evaluation and assessment are not organized effectively. Short and long term measures to overcome the math learning problems of the prospective engineers are indicated in respect to the basic educational principles. Experience in this line is shared - computer-based training aids and tests, compulsory term papers and consultations for the students with lower scores, teamwork is recommended. The long-term measures involve introducing the laboratory exercises, teacher's teams from different departments and faculties for common training materials and classes, joint work with faculty and students; attracting and training of good teachers and continuous improvement of their qualification.